2020
DOI: 10.1111/cas.14571
|View full text |Cite
|
Sign up to set email alerts
|

Cancer‐associated mutations in normal human endometrium: Surprise or expected?

Abstract: The endometrium is a unique component of the uterus characterized by cyclic regeneration during menstrual cycles. After shedding during menstruation, the endometrium vigorously regenerates during a 14-d proliferative phase, followed by a secretory change persisting until the next menstruation. Endometriosis is a disease experienced by many women of reproductive age in which the uterine endometrium grows outside the uterus. It is accompanied by a variety of complications, including dysmenorrhea, pelvic pain, and Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 46 publications
3
19
0
Order By: Relevance
“…Several studies, including by our group, have recently reported that representative oncogenes of human cancers, such as KRAS and PIK3CA , are frequently mutated in ovarian endometriosis, 12 deep infiltrating endometriosis, 13 and iatrogenic endometriosis 14 . Moreover, those oncogenes have also been identified in normal endometrium 12,15‐18 . In our study, KRAS was most frequently mutated in ovarian endometriosis, with 23/54 (42.6%) of endometriosis cases harboring somatic KRAS mutations 12 .…”
Section: Introductionsupporting
confidence: 62%
“…Several studies, including by our group, have recently reported that representative oncogenes of human cancers, such as KRAS and PIK3CA , are frequently mutated in ovarian endometriosis, 12 deep infiltrating endometriosis, 13 and iatrogenic endometriosis 14 . Moreover, those oncogenes have also been identified in normal endometrium 12,15‐18 . In our study, KRAS was most frequently mutated in ovarian endometriosis, with 23/54 (42.6%) of endometriosis cases harboring somatic KRAS mutations 12 .…”
Section: Introductionsupporting
confidence: 62%
“…Considering that isolated driver mutations of ARID1A or PIK3CA transduced into normal endometrial epithelium have no gross phenotypes, but in combination, the atypical phenotype arises [ 30 ], a similar requirement may apply to expose the phenotype of KRAS mutation in the endometrial epithelium. Moreover, in normal endometrium and in ovarian endometrioma, similar driver mutations are found; however, the mutant allele frequency is higher in the latter [ 17 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the process of epithelial-to-mesenchymal transition (EMT) seems to be crucial in the development of adenomyosis but also plays an important role in carcinogenesis [ 31 , 32 ]. Several studies have shown that changes in genes like AT-rich interactive domain-containing protein 1A (ARID1A), PTEN, KRAS, phosphatidylinositol-4,5-bisphosphate 3-kinase, catalytic subunit alpha (PIK3CA) and Serine/threonine-protein phosphatase 2A 65 kDa regulatory subunit A alpha isoform (PPP2R1A) are present in women with endometriosis, but these are also known cancer-driving mutations involved in endometrial cancer carcinogenesis [ 33 , 34 ]. However, cancer-associated mutations were also found in endometriotic lesions without concurrent cancer, in particular in deep infiltrating lesions which are rarely associated with cancer development [ 35 ].…”
Section: Discussionmentioning
confidence: 99%